2007
DOI: 10.1002/14651858.cd004929.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic nasogastric decompression after abdominal surgery

Abstract: BackgroundRoutine use of nasogastric tubes after abdominal operations is intended to hasten the return of bowel function, prevent pulmonary complications, diminish the risk of anastomotic leakage, increase patient comfort and shorten hospital stay. ObjectivesTo investigate the efficacy of routine nasogastric decompression after abdominal surgery in achieving each of the above goals. Search methodsSearch terms were nasogastric, tubes, randomised, using MEDLINE, EMBASE, Cochrane Central Register of Controlled Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(55 citation statements)
references
References 33 publications
0
50
0
5
Order By: Relevance
“…Many clinical studies have suggested that this practice does not provide any benefit but could increase patient discomfort and respiratory complications [1][2][3]. Furthermore, three recent meta-analyses concluded that nasogastric or nasojejunal decompression does not promote the recovery of gastrointestinal function or reduce the incidence of postoperative complications after gastrectomy for gastric cancer and after abdominal surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical studies have suggested that this practice does not provide any benefit but could increase patient discomfort and respiratory complications [1][2][3]. Furthermore, three recent meta-analyses concluded that nasogastric or nasojejunal decompression does not promote the recovery of gastrointestinal function or reduce the incidence of postoperative complications after gastrectomy for gastric cancer and after abdominal surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some studies have shown a lower incidence of atelectasis and pulmonary complications in patients who did not undergo NG decompression [12]. The routine postoperative use of an NG catheter is reportedly unnecessary in most major abdominal operations in children [11,12]. An NG catheter was used routinely in our series, and the routine catheter withdrawal time varied depending on the surgeon's preference despite the lack of other influencing factors, such as intestinal adhesions.…”
Section: Discussionmentioning
confidence: 89%
“…Surgeons classically use an NG catheter to speed up the return of bowel function after abdominal surgery, prevent lung complications, reduce the risk of anastomotic leakage, increase patient comfort, and shorten the inpatient period [11]. These theoretical advantages have not been supported by properly planned studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results are contrasted by a survey of general surgeons, who use nasogastric tubes less frequently, and are supported by more robust evidence specific to their specialty. 3,17 The use of both postoperative nasogastric tubes and nonabdominal drains are areas of perioperative management that would therefore benefit from focused research in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2 Attempts in specialties such as general surgery have been made to create a perioperative practice that reflects current evidence. [3][4][5] For example, the Enhanced Recovery After Surgery (ERAS) Society was formed to aggregate various evidence-practice gaps into a "multimodal perioperative care pathway designed to achieve early recovery for patients undergoing major surgery." 6 The ERAS Society has published 3 specific guidelines for perioperative practice specific to the practice of general surgery.…”
mentioning
confidence: 99%